2020
DOI: 10.1007/s40430-020-02541-w
|View full text |Cite
|
Sign up to set email alerts
|

Research nonlinear vibrations of a dual-rotor system with nonlinear restoring forces

Abstract: A dual-rotor system is a core component of an aero-engine, and it is very important to study the nonlinear vibrational characteristics for the aero-engine's development. Based on analyzing structural characteristics of aero-engine's rotors, a novel and more practical dual-rotor dynamic coupling model with nonlinear restoring forces of high-pressure and low-pressure rotors is first proposed. In the linear dynamic coupling model, the coupling critical speed, natural frequencies and vibration responses of the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The mass and moment of the inertia of the shaft section are placed on the nodes at both ends. (2) The supports are considered as spring elements without cross stiffness and damping. (3) The fan disc, low-pressure turbine disc, high-pressure compressor disc, and high-pressure turbine disc are simplified as hollow discs, which are regarded as rigid bodies with rotation effects.…”
Section: Finite Element Model Of the Dual-rotor System With Four Disc...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mass and moment of the inertia of the shaft section are placed on the nodes at both ends. (2) The supports are considered as spring elements without cross stiffness and damping. (3) The fan disc, low-pressure turbine disc, high-pressure compressor disc, and high-pressure turbine disc are simplified as hollow discs, which are regarded as rigid bodies with rotation effects.…”
Section: Finite Element Model Of the Dual-rotor System With Four Disc...mentioning
confidence: 99%
“…Exploring a simplified model of the dual-rotor system that can reflect the structural characteristics and dynamic behavior of the aero-engine is the key to establishing an accurate and efficient dynamic model of rotor system for aero-engine. The model of the double rotors and multi-supports system used in the current research mainly includes the following types: the dual-rotor system with one disc for the high-pressure rotor and one disc for the low-pressure rotor [1][2][3][4], the dual-rotor system with two discs for the high-pressure rotor and two discs for the low-pressure rotor [5][6][7], and the dual-rotor system with multiple-discs [4,[8][9][10]. The rigid-flexible coupling of rotor system structure is not considered in dynamic modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of speed ratio, unbalanced excitation and inter-shaft bearing's clearance in the radial direction on the system's amplitude-frequency characteristics was demonstrated. Liu et al 23 suggested a dynamic model with two different pressure rotors; the critical speed, vibration frequency, and LP rotor's vibration responses were investigated. Lu et al 24 investigated the nonlinear properties of a dual-rotor system connected with an inter-shaft bearing and unbalanced excitations, vertical static forces, and gravities to establish the system's motion equations.…”
Section: Introductionmentioning
confidence: 99%